Neither fugitive nor free : Atlantic slavery, freedom suits, and the legal culture of travel - Wong, Edlie L. (America and the long 19th century., 2009)
Studies lawsuits to gain freedom for slaves on the grounds of their having traveled to free territory, starting with Somerset v. Stewart (England, 1772), Commonwealth v. Aves (Massachusetts, 1836), Dred Scott v. Sanford, and cases brought questioning the legitimacy of Negro Seamen Acts in the antebellum coastal South. These lawsuits and accounts of them are compared to fugitive slave narratives to shed light on both. The differing impact of freedom obtained from such suits for men and women (women could claim that their children were free, once they were judged free) is examined.